Evaluasi perlakuan akuntansi di badan pengelolaan keuangan dan pendapatan daerah Kota Tomohon - Jocom, Agnes Michelle; Budiarso, Novi Swandari; Afandi, Dhullo (Yayasan Widyantara Nawasena Raharja, 2024)
Government Regulation Number 71 of 2010 sets out the government accounting standards that must be applied in preparing and presenting government financial reports. This study will evaluate the suitability of the accounting treatment related to the presentation and disclosure of financial statements based on government accounting standards in Government Regulation Number 71 of 2010 at the Tomohon City Regional Revenue and Financial Management Agency. This study employs a descriptive qualitative approach, utilising both interview and documentation data collection techniques. The findings indicate that the majority of financial statements presented and disclosed have been prepared in accordance with Government Regulation Number 71 of 2024. However, there are still discrepancies in the disclosure of balance sheet details.